Characteristics of accidental injuries from power tools treated at two emergency departments in Queensland. (8th November 2018) - Judge, Chantelle; Eley, Rob; Miyakawa‐Liu, Monica; Brown, Nathan J; McCosker, Laura; Livesay, Georgia; Hughes, James A; Vallmuur, Kirsten
Abstract: Objective: Injuries are a major burden on the Australian healthcare system. Power tool usage is a common cause of accidental injury. A better understanding of the trends of power tool injuries will inform prevention strategies and potentially mitigate costs. Methods: The ED databases from two level 1 hospitals were reviewed for presentations between 2005 and 2015 resulting from accidental injury with power tools. A subgroup of patients presenting to one hospital between 2016 and 2017 were interviewed about the activities and circumstances that led to their injuries, and followed up 3 months later to assess outcomes. Results: A total of 4057 cases of accidental injury from power tool use were identified. Power saws and grinders contributed to 54% of injuries. Most injuries were located on an upper limb (48%) or the head and neck (30%). Over half (54%) of all head injuries were associated with metal and wood fragments to the eye from grinders, drills and saws. Hospital admission rates were highest for patients aged >60 years. Injuries to females were <5% of all presentations, but 40% of those caused by lawnmowers. Among the 200 patients interviewed, lapses in concentration during use, and modification and inappropriate use of a power tool were the main contributors to injury. Recovery periods >3 months were common. Conclusions: Accidental injuries from power tool use have a considerable impact on ED resources and can affect the long‐term quality of life of those injured. Effective education about safe usage and protection may prevent many injuries.